2019
DOI: 10.4103/jovr.jovr_260_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of tear function tests, tear osmolarity, and conjunctival impression cytology between patients with pterygium and healthy eyes

Abstract: Purpose: To compare histologic abnormalities of tear film and tear osmolarity between normal eyes and eyes with pterygium. Methods: This was a prospective, hospital-based, case–control study involving 95 patients (65 men, 30 women) with unilateral pterygium. The tear meniscus height (TMH), Schirmer's test-1 (SCH-1) score, Rose Bengal staining (RBS) score, tear film breakup time (TBUT), tear osmolarity (TO), and conjunctival impression cytology (CIC) were assessed in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Rivas et al 23 investigated the topographic distribution of goblet cells with impression cytology and reported densities of 331±148/mm 2 in the superior bulbar conjunctiva and 427±112/mm 2 in the inferior bulbar conjunctiva. Although Chan et al 8 demonstrated that goblet cell density increased with squamous metaplasia in pterygium tissue, a decrease in goblet cell density was observed in studies by Safarzadeh et al 24 and Julio et al 30 Labbé et al 31 explained that the change in the number of goblet cells is related to pterygium activity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Rivas et al 23 investigated the topographic distribution of goblet cells with impression cytology and reported densities of 331±148/mm 2 in the superior bulbar conjunctiva and 427±112/mm 2 in the inferior bulbar conjunctiva. Although Chan et al 8 demonstrated that goblet cell density increased with squamous metaplasia in pterygium tissue, a decrease in goblet cell density was observed in studies by Safarzadeh et al 24 and Julio et al 30 Labbé et al 31 explained that the change in the number of goblet cells is related to pterygium activity.…”
Section: Discussionmentioning
confidence: 96%
“…Impression cytology specimens were graded as normal or abnormal for epithelial cell density, goblet cell density, and mucin spots (goblet cell secretions). 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a duration of five minutes, the extent of wetting was measured in millimeters. A result of less than 10 mm was deemed abnormal [ 18 ]. Before the TBUT measurement, the precorneal tear film was stained with fluorescein.…”
Section: Methodsmentioning
confidence: 99%
“…Pterygia can affect vision and cause redness, foreign body sensation, decreased tear lm stability, and affected patients frequently have dry eye disease (DED) symptoms [4].…”
Section: Introductionmentioning
confidence: 99%